Charge-Voltage curves of surge corona on transmission lines two measurement methods. - Noda, T.
This paper investigates the charge versus voltage (q-v) curves of surge corona on transmission lines. Two measurement methods of the q-v curves are proposed, and field test results are shown to validate the methods. Since the new methods do not require a charge-measuring conductor, such as a corona cage, the q-v curves are measured in the real electric-field distribution. One of the methods obtains the amount of charges q by numerically integrating the digitally stored waveform of injected current, assuming that the line is short in length and open ended. Thus, it is suitable for measurement using an experimental setup. The other calculates q from voltage and current waveforms based on the traveling-wave theory, assuming that the line is long enough to expect no reflected waves, and it is applicable to existing "real" transmission lines. Measured q-v curves are compared with simulated ones, and their physical properties are discussed in the paper.
Keywords: Charge-measuring conductor; Charge-voltage curves; Corona cage; Current waveforms; Electric field distribution; Measurement methods; Power transmission lines surge corona; Q-v curves; Traveling-wave theory; Voltage waveforms